Precision Tailoring Quasi-BIC Resonance of a-Si:H Metasurfaces - Athira Kuppadakkath; Ángela Barreda; Lilit Ghazaryan; Tobias Bucher; Kirill Koshelev; Thomas Pertsch; Adriana Szeghalmi; Duk Choi; Isabelle Staude; Falk Eilenberger (Nanomaterials, 2023)
The capability of tailoring the resonance wavelength of metasurfaces is important as it can alleviate the manufacturing precision required to produce the exact structure according to the design of the nanoresonators. Tuning of Fano resonances by applying heat has been theoretically predicted in the case of silicon metasurfaces. Here, we experimentally demonstrate the permanent tailoring of quasi-bound states in the continuum (quasi-BIC) resonance wavelength in an a-Si:H metasurface and quantitatively analyze the modification in the Q-factor with gradual heating. A gradual increment in temperature leads to a spectral shift in the resonance wavelength. With the support of ellipsometry measurements, the spectral shift resulting from the short-duration (ten minutes) heating is identified to be due to refractive index variations in the material rather than a geometric effect or amorphous/polycrystalline phase transition. In the case of quasi-BIC modes in the near-infrared, resonance wavelength could be adjusted from T = 350 °C to T = 550 °C without affecting the Q-factor considerably. Apart from the temperature-induced resonance trimming, large Q-factors can be attained at the highest analyzed temperature (T = 700 °C) in the near-infrared quasi-BIC modes. Resonance tailoring is just one of the possible applications of our results. We expect that our study is also insightful in the design of a-Si:H metasurfaces where large Q-factors are required at high temperatures.